THE SPECIFICITY OF EMOTIONAL LABOR OF SOCIAL WORKERS HELPING CHILDREN - Tarkhanova, Irina; Koryakovtseva, Olga; Zhedunova, Lyudmila; Upeniece, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the results of the study of the emotional perception of clients conducted among Russian social workers who help children. The research is based on the concept of the role of emotional labor in professional activities. At the same time, we proceed from the understanding that the content and volume of emotional labor depends on the type of clients of social workers: its specificity when working with children will not be the same as when working with adults. The results of the research show that social workers who help children have difficulties in regulating emotions when interacting with clients, and therefore in assessing children's actions and behavior. The results of the study show that the effectiveness of emotional labor of social workers helping children depends on the level of knowledge of the age characteristics of children and the pedagogical mechanisms of communicating with them. We conclude that we should pay more attention to the role of emotional labor in everyday social work with children.